Long-term protection materials for diversified grounding monitoring components of power distribution systems

By using silicone modified water-soluble acrylic resin and graphite phase carbon nitride nanosheets and carbon nanotubes in the ground protection material, the problem that existing materials are difficult to ensure conductivity, corrosion resistance and corrosion resistance at the same time is solved, and a more efficient ground protection effect is achieved.

CN116656195BActive Publication Date: 2025-03-25LUOHE POWER SUPPLY OF HENAN ELECTRIC POWER CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310625809.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-30
Publication Date
2025-03-25
Estimated Expiration
2043-05-30

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention provides a long-term protective material for diversified grounding monitoring components of a power distribution system, and belongs to the technical field of protective materials. A long-term protective material for diversified grounding monitoring components of a power distribution system, the raw materials for its preparation include, by weight: 100 parts of organosilicon-modified water-soluble acrylic resin, 8-12 parts of polyvinyl alcohol, 15-25 parts of graphite phase carbon nitride nanosheets, 1-7 parts of carbon nanotubes, 2-8 parts of polydopamine, 0.5-3 parts of surfactant, 10-20 parts of curing agent, and 12-21 parts of solvent. The protective material of the present invention is used for coating to achieve long-term protection of diversified grounding monitoring components to cope with the more complex demands currently faced by diversified grounding monitoring.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of protective materials, and in particular relates to a long-term protective material for a diversified grounding monitoring component of a power distribution system. Background Art

[0002] At present, a high proportion of new energy and power electronic equipment are widely connected, and the power grid presents new characteristics of complex hybrid connection of strong and weak electricity, AC and DC. Especially with the large-scale application of power electronic devices, the ground current mainly composed of equipment leakage current, induced current, soil stray current and loop current will show diversified characteristics. The construction of a new power system will expand the scale of the original power system, resulting in a corresponding increase in the ground current level of the entire system.

[0003] The new power system has a relatively large system architecture, covering areas with high soil resistivity, high salinity, strong acid and alkali, and coastal areas with strong corrosion, which puts higher requirements on the anti-corrosion performance of grounding materials. At the same time, as the scale of the power grid in the new power system increases, the amplitude of the fault current entering the ground will also increase, which places higher and higher requirements on the electrical performance of the grounding device.

[0004] With the increase of voltage level, transmission capacity and system scale of transmission lines, the fault current entering the ground of power systems has also increased accordingly, resulting in higher and higher requirements for the stability of grounding devices. In addition to traditional galvanized steel as the main application material, copper-clad steel, stainless steel-clad steel, graphite-based flexible grounding materials have entered the grounding market, occupying an important share in technical transformation projects. However, with the development and application of new power systems, more stringent requirements are placed on the performance of grounding materials, especially the anti-corrosion and resistance reduction performance of grounding devices. Due to the increasing complexity of geological structure and geographical environment, the overall operating environment has brought serious challenges to the anti-corrosion and resistance reduction effects of grounding materials. Therefore, it is of great significance to develop efficient grounding resistance reduction and anti-corrosion technologies and materials to provide more comprehensive technical support for the design, operation and maintenance of grounding technologies under new power systems.

[0005] Graphitic carbon nitride (g-C3N4) is a new type of carbon-based inorganic material. Since its introduction in 2012, it has attracted extensive attention from researchers for its inherent high light absorption and light responsiveness, semiconductor properties, physiological stability and good biocompatibility. Existing studies have found that graphitic carbon nitride used in coatings also has good anti-corrosion and anti-fouling properties. For example, patent document CN115216201A provides an anticorrosive coating with photocatalytic antibacterial effect, including epoxy resin, epoxy resin modifier, multifunctional rheological additive, curing agent and organic-inorganic hybrid modified g-C3N4 nanosheets, wherein the organic-inorganic hybrid modified g-C3N4 nanosheets are obtained by coating the surface of g-C3N4 nanosheets with polydopamine and then surface-modifying them with a composite coupling agent; the g-C3N4 nanosheets are obtained by exfoliating bulk-C3N4, a graphite-like carbon nitride; the preparation method is as follows: S1, epoxy resin, polyvinyl butyral resin, multifunctional rheological additive and mixed solvent are added to a high-speed disperser, and after high-speed uniform dispersion, pigments and fillers and organic-inorganic hybrid modified g-C3N4 nanosheets are added to continue high-speed dispersion, and after dispersion is completed, liquid A is obtained. S2, cardanol modified amine adducts and tackifiers are dispersed at high speed, and liquid B is obtained after dispersion is completed. S3. Mix liquid A and liquid B to obtain the anticorrosive coating with photocatalytic antibacterial effect. After inspection, the coating can meet the needs of integrated anticorrosion and antifouling of coatings, and solve the problem of poor coating effect of nano-photocatalytic fillers in coatings, effectively improve the photocatalytic antifouling and anticorrosion performance of coatings, reduce the cost of coatings, and have wide applicability to different substrates, good compatibility, strong versatility, improve the efficiency and benefits of shipbuilding coatings; and can also be widely used in long-term anticorrosion coatings for offshore facilities, bridges, pipelines, storage cabinets, steel structures, etc., with a wide range of applications. However, there are still some shortcomings in the use of the above-mentioned coatings for grounding protection materials, and the conductivity, corrosion resistance and other aspects of the grounding materials cannot be effectively guaranteed. Summary of the invention

[0006] In view of this, the technical problem to be solved by the present invention is to provide a long-term protective material for diversified grounding monitoring components of a power distribution system.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is: a long-term protective material for diversified grounding monitoring components of a distribution system, wherein the raw materials for its preparation include, by weight: 100 parts of silicone-modified water-soluble acrylic resin, 8-12 parts of polyvinyl alcohol, 15-25 parts of graphite phase carbon nitride nanosheets, 1-7 parts of carbon nanotubes, 2-8 parts of polydopamine, 0.5-3 parts of surfactant, 10-20 parts of curing agent, and 12-21 parts of solvent.

[0008] Preferably, the surfactant is at least two of a coupling agent, a wetting agent, a dispersant and an adhesion promoter.

[0009] The diameter of the aggregated nanomaterials treated with the above surfactants is significantly reduced, which improves the fluidity of the system and greatly improves the processing performance, gloss, brightness, adhesion and other apparent quality properties of the product. Moreover, different types of surfactants have different effects, and scientific mixing can complement each other and achieve more significant expected results.

[0010] Preferably, the solvent is at least one of methanol, isopropanol, ethylene glycol and triethylamine.

[0011] The present invention also provides a method for preparing the long-term protective material for the diversified grounding monitoring component of the power distribution system, comprising the following steps:

[0012] The following raw materials are provided: organic silicon modified water-soluble acrylic resin, polyvinyl alcohol resin, graphite phase carbon nitride nanosheets, carbon nanotubes, polydopamine, surfactant, curing agent and solvent;

[0013] Slowly adding graphite phase carbon nitride nanosheets into a polyvinyl alcohol solution, stirring evenly, and ultrasonically treating to obtain a first mixed solution; then adding carbon nanotubes into the first solvent, stirring well, to obtain a second mixed solution; slowly adding the second mixed solution into the first mixed solution, stirring evenly, to obtain a third mixed solution; subjecting the third mixed solution to constant temperature heating and reflux, passing circulating cooling water to maintain a constant temperature, cooling naturally to room temperature after the reaction is completed, washing with deionized water and ethanol for multiple times, drying, grinding and sieving, to obtain a composite material;

[0014] The composite material is mixed with polydopamine, a surfactant and a second solvent, stirred evenly, and subjected to ultrasonic treatment; finally, an organosilicon-modified water-soluble acrylic resin and a curing agent are added, mixed, and stirred evenly to obtain a protective material.

[0015] Preferably, the concentration of the polyvinyl alcohol solution is 8-12 mg / L;

[0016] The first solvent is methanol;

[0017] The second solvent is at least one of isopropanol, ethylene glycol and triethylamine;

[0018] The mass ratio of the first solvent to the second solvent is 1:2.

[0019] Preferably, the ultrasonic treatment is performed for 4-6 hours at a power of 500-600W.

[0020] Preferably, the process parameters of the constant temperature heating reflux include: temperature 72-75° C., time 15-24 h.

[0021] The present invention composites graphite phase carbon nitride with carbon nanotubes through the above method, which can make the above two nanoparticles more evenly dispersed in the resin matrix, inhibit the agglomeration of nanoparticles, thereby giving full play to the inherent advantages of nanomaterials and significantly enhancing the conductivity and corrosion resistance of the resin.

[0022] Graphite carbon nitride has the characteristics of appropriate band gap, good oxidation ability, excellent photochemical and thermal stability. Carbon nitride is composed of α phase, β phase, cubic phase, quasi-cubic phase and graphite-like structure, and its band gap width is 5.49, 4.85, 4.13, 4.30, 2.7eV respectively. Among them, graphite-like carbon nitride has been widely used in various photocatalytic fields due to its own band gap width and adjustable band structure. Graphite carbon nitride has a two-dimensional layered structure similar to graphite stacking, and it has been proved that two different polymer structures can be used as the basic structural unit of each sheet. These basic units are connected by terminal N atoms to form an infinitely extended plane. At present, there are two types of graphite carbon nitride nanomaterials: s-triazine unit and 3-s-triazine unit. Among them, the graphite carbon nitride nanomaterial based on 3-s-triazine unit is more stable and has become a graphite carbon nitride nanomaterial that is currently studied more.

[0023] Zuo et al. (Zuo S, Chen Y, Liu W, et al. Polyaniline / g-C3N4 composites as novel media for anticorrosion coatings[J]. Journal of Coatings Technology and Research, 2017, 14:1307-1314.) prepared PANI / g-C3N4 nanocomposite coatings by chemical oxidative polymerization, which showed excellent anti-penetration ability and corrosion inhibition performance in salt solution. Madhan Kumar et al. (Madhan Kumar A, Yusuf Khan M, Suleiman RK, et al. Promising graphitic carbon nitride / MoO x nanocomposites: For surface protective performance of AA2024 alloys inmarine environment [J]. Surface and Coatings Technology, 2019, 374:579-590.) Using molybdenum oxide (MoO x ) modified g-C3N4, and rod-shaped MoO was loaded on the g-C3N4 layered surface xNanoparticles were then uniformly dispersed into epoxy resin. x After the nanoparticles are added, the surface protection and corrosion resistance of the coating are significantly enhanced, preventing the penetration of foreign electrolytes, coating degradation and delamination, and having no effect on the coating's adhesion to the aluminum substrate. Therefore, compounding graphite phase carbon nitride with specific components can play a role in enhancing anti-corrosion and corrosion inhibition properties.

[0024] Carbon nanotubes play a very important role in various fields of society with their unique properties. The structural properties of carbon nanotubes, such as closed ports and large aspect ratio, make them have high strength and Young's modulus. For example, under the same volume conditions, its strength is 100 times that of steel, while its mass is only 1 / 6 of that of steel. In particular, its structure will not deform under the action of high external forces; carbon nanotubes have good toughness, and their elastic modulus is comparable to that of diamond, with a maximum of about 1Tpa; carbon nanotubes also have a large specific surface area, so they have good adsorption properties and interface effects, and carbon nanotubes are also very good electrical and thermal conductive materials.

[0025] The research on carbon nanotubes is currently the most eye-catching in the field of nanomaterial research. It has a series of advantages: high mechanical strength, large specific surface area, high electrical conductivity, strong interface effect, etc., and has a wide range of applications in various fields of society due to its special mechanical, physical, and chemical properties. However, carbon nanotubes have strong intermolecular forces between themselves and are very easy to agglomerate, which seriously affects their ability to disperse evenly in materials and other solvents, which in turn greatly limits their application.

[0026] Therefore, in order to solve the above-mentioned practical problems, the present invention realizes graphite phase carbon nitride loading carbon nanotubes through pretreatment and heating reflux, and uses the product to make grounding protection materials. Compared with the single use of graphite phase carbon nitride or carbon nanotubes, the conductivity, corrosion resistance or thermal stability performance is more significant.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] The present invention provides a long-term protective material for diversified grounding monitoring components of a power distribution system through the above technical solution. Long-term protection of diversified grounding monitoring components is achieved by coating the above material to cope with the more complex demands currently faced by diversified grounding monitoring.

[0029] The present invention uses resin as the matrix material, preferably a water-soluble acrylic resin modified with silicone; at the same time, the added graphite phase carbon nitride is compounded with carbon nanotubes to overcome the agglomeration problem in the mixing process, make it more evenly dispersed, and enhance the conductivity and corrosion resistance of the composite material; through experiments, it is found that the above two raw materials have better miscibility with the matrix material after compounding, and the appearance and adhesion of the prepared coating material are also more significant. In order to cooperate with the role of the above composite material, the present invention also preferably uses a specific surfactant. After being treated with the surfactant, the diameter of the aggregated particles is significantly reduced, so that the fluidity of the system is improved, and the processing performance of the product, gloss, brightness, adhesion and other apparent quality properties are greatly improved. Moreover, different types of surfactants have different effects, and scientific mixing can complement each other to achieve more significant expected results. The present invention preferably uses at least two of a coupling agent, a wetting agent, a dispersant and an adhesion promoter; more preferably, a wetting agent and a dispersant are used in combination; the coupling agent can be selected from one or both of a titanate coupling agent and a silane coupling agent; the wetting agent can be selected from an organosilicon wetting agent MY245, an aqueous wetting agent BESM®2411 or an alkylphenol polyoxyethylene ether surfactant; the dispersant can be selected from a hyperdispersant, such as Solplus™ hyperdispersant, an aqueous nanoparticle dispersant MALIALIM ® FA series products; the adhesion promoter can be a water-based adhesion promoter, such as EasyTech GT-2000 and HY-200. The present invention can make the two nanomaterials, graphite phase carbon nitride and carbon nanotubes, dispersed more evenly in the resin matrix through the combination of the above raw materials, inhibit the agglomeration of nanoparticles, and enhance the conductivity and corrosion resistance of the resin.

[0030] The present invention realizes graphite phase carbon nitride loading carbon nanotubes through pretreatment and heating reflux, and uses the product to make grounding protection materials. Compared with the single use of graphite phase carbon nitride or carbon nanotubes, the conductivity and corrosion resistance are more significant. The protection material of the present invention can be directly coated on the outer surface of the grounding monitoring component, and the thickness can be selected to be 100-300 microns. DETAILED DESCRIPTION

[0031] In order to better understand the present invention, the content of the present invention is further clearly set forth in conjunction with the embodiments below, but the protection content of the present invention is not limited to the following embodiments. In the following description, a large number of specific details are provided in order to provide a more thorough understanding of the present invention. However, it is obvious to those skilled in the art that the present invention can be implemented without one or more of these details.

[0032] Unless otherwise specified, all raw materials are from commercially available products and do not contain other unspecified components except inevitable impurities unless otherwise specified.

[0033] A long-term protective material for diversified grounding monitoring components of a power distribution system. The raw materials for its preparation include, by weight: 100 parts of organic silicon modified water-soluble acrylic resin, 8-12 parts of polyvinyl alcohol, 15-25 parts of graphite phase carbon nitride nanosheets, 1-7 parts of carbon nanotubes, 2-8 parts of polydopamine, 0.5-3 parts of surfactant, 10-20 parts of curing agent, and 12-21 parts of solvent.

[0034] In some embodiments of the present invention, the performance indicators of the organosilicon-modified water-soluble acrylic resin are as follows: Appearance: light yellow transparent viscous liquid, solid content: (65±2)%, viscosity: 10000-15000cps / 25°C.

[0035] Graphite phase carbon nitride nanosheets can be prepared according to the following literature (Chen Qi, Xu Shihong, Li Ye. Preparation and performance study of graphite phase carbon nitride nanosheets [J]. Journal of Wuhan University of Technology, 2015, 37(9):5.).

[0036] The surfactant is at least one of a coupling agent, a wetting agent, a dispersant and an adhesion promoter;

[0037] Wherein: the coupling agent can be selected from one or both of titanate coupling agent and silane coupling agent;

[0038] Wetting agents can be selected from silicone wetting agent MY245, water-based wetting agent BESM®2411 or alkylphenol polyoxyethylene ether surfactants;

[0039] Dispersants can be selected from hyperdispersants, such as Solplus™ hyperdispersants, aqueous nanoparticle dispersants MALIALIM ® FA series products;

[0040] Adhesion promoters can be water-based adhesion promoters, such as EasyTech GT-2000 and HY-200.

[0041] The diameter of the aggregated nanomaterials treated with the above surfactants is significantly reduced, which improves the fluidity of the system and greatly improves the processing performance, gloss, brightness, adhesion and other apparent quality properties of the product. Moreover, different types of surfactants have different effects, and scientific mixing can complement each other and achieve more significant expected results.

[0042] In some embodiments of the present invention, the curing agent may be selected from tetraisopropyl titanate or isophorone diisocyanate.

[0043] The solvent is at least one of methanol, isopropanol, ethylene glycol and triethylamine.

[0044] The present invention also provides a method for preparing the long-term protective material for the diversified grounding monitoring component of the power distribution system, comprising the following steps:

[0045] The following raw materials are provided: organic silicon modified water-soluble acrylic resin, polyvinyl alcohol resin, graphite phase carbon nitride nanosheets, carbon nanotubes, polydopamine, surfactant, curing agent and solvent;

[0046] Slowly adding graphite phase carbon nitride nanosheets into a polyvinyl alcohol solution, stirring evenly, and ultrasonically treating to obtain a first mixed solution; then adding carbon nanotubes into the first solvent, stirring well, to obtain a second mixed solution; slowly adding the second mixed solution into the first mixed solution, stirring evenly, to obtain a third mixed solution; subjecting the third mixed solution to constant temperature heating and reflux, passing circulating cooling water to maintain a constant temperature, cooling naturally to room temperature after the reaction is completed, washing with deionized water and ethanol for multiple times, drying, grinding and sieving, to obtain a composite material;

[0047] The composite material is mixed with polydopamine, a surfactant and a second solvent, stirred evenly, and subjected to ultrasonic treatment; finally, an organosilicon-modified water-soluble acrylic resin and a curing agent are added, mixed, and stirred evenly to obtain a protective material.

[0048] In some preparation schemes, the concentration of the polyvinyl alcohol solution is 8-12 mg / L, preferably 10 mg / L; the first solvent is methanol; the second solvent is at least one of isopropanol, ethylene glycol and triethylamine; and the mass ratio of the first solvent to the second solvent is 1:2.

[0049] In some preparation schemes, the ultrasonic treatment time is 4-6 hours, and the power is 500-600W; for example: time 4 hours, power 600W; time 5 hours, power 550W; time 6 hours, power 400W.

[0050] In some preparation schemes, the process parameters of constant temperature heating reflux include: temperature 72-75°C, time 15-24h; for example: temperature 72°C, time 24h; temperature 73°C, time 20h; temperature 75°C, time 15h.

[0051] The washing times with deionized water or ethanol can be 2 times, 3 times or 4 times.

[0052] Examples 1-6

[0053] Table 1 Raw material composition of Examples 1-6

[0054]

[0055] Among them, tetraisopropyl titanate is selected as the curing agent.

[0056] Table 2 Composition of surfactants

[0057]

[0058] Wherein: the coupling agent is a titanate coupling agent;

[0059] Wetting agent: alkylphenol polyoxyethylene ether surfactant;

[0060] Solplus™ hyperdispersant was selected as the dispersant;

[0061] The adhesion promoter should be HY-200.

[0062] Table 3 Composition of solvents

[0063]

[0064] Example 7

[0065] A method for preparing a long-term protective material for a diversified grounding monitoring component of a power distribution system comprises the following steps: providing raw materials according to Tables 1-3 respectively; slowly adding graphite phase carbon nitride nanosheets to a 10 mg / L polyvinyl alcohol solution, stirring evenly, and ultrasonically treating to obtain a first mixed solution; then adding carbon nanotubes to the first solvent, stirring sufficiently to obtain a second mixed solution; slowly adding the second mixed solution to the first mixed solution, stirring evenly, and obtaining a third mixed solution; subjecting the third mixed solution to constant temperature heating and reflux, passing circulating cooling water to maintain a constant temperature, cooling naturally to room temperature after the reaction is completed, washing with deionized water and ethanol for 3 times, drying, grinding and sieving to obtain a composite material; mixing the composite material with polydopamine, a surfactant and a second solvent, stirring evenly, and ultrasonically treating; finally adding an organosilicon-modified water-soluble acrylic resin and a curing agent, mixing, stirring evenly, and obtaining a protective material; wherein:

[0066] The ultrasonic treatment time was 5 h, and the power was 550 W;

[0067] The process parameters of constant temperature heating reflux include: temperature 75°C, time 21h.

[0068] Comparative Example 1: A long-term protective material for a diversified grounding monitoring component of a power distribution system, wherein the raw materials for its preparation include, by weight: 100 parts of a water-soluble acrylic resin modified with silicone, 23 parts of graphite carbon nitride nanosheets, 4 parts of carbon nanotubes, 2.0 parts of a surfactant, 18 parts of a curing agent, and 12 parts of a second solvent. The above-mentioned surfactant, curing agent and solvent are the same as those in Example 6. The preparation method thereof comprises the following steps: dissolving the water-soluble acrylic resin modified with silicone in a second solvent, adding a surfactant and stirring evenly, then adding graphite carbon nitride nanosheets and carbon nanotubes in turn, stirring evenly, and ultrasonically treating for 5 hours at a power of 550W; finally, adding a curing agent and stirring evenly, curing, and obtaining a protective material.

[0069] Comparative Example 2: This comparative example is different from Example 6 in that the first solvent and polyvinyl alcohol are omitted. The specific preparation method is: dissolving the organosilicon-modified water-soluble acrylic resin in the second solvent, adding polydopamine and a surfactant and stirring evenly, then adding graphite phase carbon nitride nanosheets and carbon nanotubes in sequence, stirring evenly, and ultrasonically treating for 5 hours at a power of 550 W; finally, adding a curing agent and stirring evenly, and curing to obtain a protective material.

[0070] Comparative Example 3: This comparative example is different from Example 6 in that the first solvent and carbon nanotubes are omitted, and the specific preparation method is: slowly adding graphite phase carbon nitride nanosheets into 10 mg / L polyvinyl alcohol solution, stirring evenly, and ultrasonically treating to obtain a mixed solution; mixing the mixed solution with polydopamine, a surfactant and a second solvent, stirring evenly, and ultrasonically treating; finally, adding silicone-modified water-soluble acrylic resin and a curing agent, mixing, stirring evenly, and obtaining a protective material; wherein: the ultrasonic treatment time is 5h, and the power is 550W.

[0071] Comparative Example 4: This comparative example is different from Example 6 in that graphene is used instead of graphite phase carbon nitride nanosheets. The specific preparation method is: slowly adding graphene to a 10 mg / L polyvinyl alcohol solution, stirring evenly, and ultrasonically treating to obtain a first mixed solution; then adding carbon nanotubes to the first solvent, stirring thoroughly to obtain a second mixed solution; slowly adding the second mixed solution to the first mixed solution, stirring evenly, and obtaining a third mixed solution; the third mixed solution is subjected to constant temperature heating and reflux, and circulating cooling water is introduced to maintain a constant temperature. After the reaction is completed, it is naturally cooled to room temperature, washed with deionized water and ethanol for 3 times, dried, ground and sieved to obtain a composite material; the composite material is mixed with polydopamine, a surfactant and a second solvent, stirred evenly, and ultrasonically treated; finally, a silicone-modified water-soluble acrylic resin and a curing agent are added, mixed, stirred evenly, and a protective material is obtained; wherein: the ultrasonic treatment time is 5h, the power is 550W; the process parameters of constant temperature heating and reflux include: temperature 75°C, time 21h.

[0072] Comparative Example 5: This comparative example differs from Example 6 in that the wetting agent is omitted, other compositions remain unchanged, and the preparation method is the same as that of Example 7.

[0073] Next, the content of the evaluation test will be described. The evaluation test was carried out on the following evaluation items.

[0074] (1) Corrosion resistance test: Typical soil in Luohe area was selected, with organic matter content <2%, pH 4.5-5.5, water content 15-25 wt%, and resistivity ≤300Ω·m;

[0075] The metal grounding grid profiles treated with coatings in Examples 1-6 and Comparative Examples 1-5 were selected, with a coating thickness of 200 microns, a burial depth of 0.5 m, and a temperature of 30° C., and subjected to a soil burial accelerated test for 6 months;

[0076] Test the corrosion rate of metal grounding grid profiles. The corrosion rate is calculated based on the weight loss of the sample before and after the test, which is converted into the material thickness change per unit time period (mm / a). In order to accurately obtain the weight loss data, the corrosion products that may be attached to the surface of the sample should generally be removed after the corrosion test. The calculation formula for the corrosion rate is as follows:

[0077] R corrosionrate =8.76×10 7 × (M-M0) / (S×T×D),

[0078] R corrosionrate -Corrosion rate, mm / a; M0-mass of the sample before the test, g; M-mass of the test after the test, g; S-total area of ​​the sample, cm 2 ; T-test time, h; D-material density, kg / m 3 .

[0079] The rating standards for corrosion rates are shown in the following table:

[0080]

[0081] (2) Conductivity test, unit: Ω.m: Use a resistivity meter to directly measure the resistivity of the protective material.

[0082] The test results of the above test are as follows:

[0083]

[0084] From the above test results, it can be seen that: 1) The grounding material of the present invention has excellent corrosion resistance under the test environment, and the protective material used can meet the anti-corrosion requirements of the grounding material and can significantly reduce the corrosion damage of the grounding material. 2) The resistivity of the protective material of the present invention is less than 5Ω·m, and it has excellent conductivity and can be used in conjunction with the grounding material. 3) Through the test results of the comparative case, it can be seen that the raw materials in the protective material of the present invention are used properly and cooperate with each other, achieving more significant anti-corrosion and conductive effects, and can be used for long-term protection of grounding monitoring components.

[0085] In addition, those skilled in the art should understand that, although there are many problems in the prior art, each embodiment or technical solution of the present invention can be improved in only one or several aspects, without having to solve all the technical problems listed in the prior art or background technology at the same time. Those skilled in the art should understand that the content not mentioned in a claim should not be used as a limitation on the claim.

[0086] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Other modifications or equivalent substitutions made to the technical solution of the present invention by ordinary technicians in the field should be included in the scope of the claims of the present invention as long as they do not depart from the spirit and scope of the technical solution of the present invention.

Claims

1. A long-term protective material for diversified grounding monitoring components of a power distribution system, characterized by: The raw materials for its preparation include, by weight: 100 parts of organic silicon modified water-soluble acrylic resin, 8-12 parts of polyvinyl alcohol, 15-25 parts of graphite phase carbon nitride nanosheets, 1-7 parts of carbon nanotubes, 2-8 parts of polydopamine, 0.5-3 parts of surfactant, 10-20 parts of curing agent, 12-21 parts of solvent, The method for preparing the long-term protective material for the diversified grounding monitoring component of the power distribution system comprises the following steps: providing the following raw materials: organic silicon modified water-soluble acrylic resin, polyvinyl alcohol, graphite phase carbon nitride nanosheets, carbon nanotubes, polydopamine, surfactant, curing agent and solvent; Slowly adding graphite phase carbon nitride nanosheets into a polyvinyl alcohol solution, stirring evenly, and ultrasonically treating to obtain a first mixed solution; then adding carbon nanotubes into the first solvent, stirring well, to obtain a second mixed solution; slowly adding the second mixed solution into the first mixed solution, stirring evenly, to obtain a third mixed solution; subjecting the third mixed solution to constant temperature heating and reflux, passing circulating cooling water to maintain a constant temperature, cooling naturally to room temperature after the reaction is completed, washing with deionized water and ethanol for multiple times, drying, grinding and sieving, to obtain a composite material; The composite material is mixed with polydopamine, a surfactant and a second solvent, stirred evenly, and subjected to ultrasonic treatment; finally, an organosilicon-modified water-soluble acrylic resin and a curing agent are added, mixed, and stirred evenly to obtain a protective material. The first solvent is methanol; the second solvent is at least one of isopropanol, ethylene glycol and triethylamine; the mass ratio of the first solvent to the second solvent is 1:

2.

2. A long-term protective material for diversified grounding monitoring components of a power distribution system as claimed in claim 1, characterized in that: The surfactant is at least two of a coupling agent, a wetting agent, a dispersant and an adhesion promoter.

3. The long-term protective material for diversified grounding monitoring components of a power distribution system according to claim 2, characterized in that: The concentration of the polyvinyl alcohol solution is 8-12 mg / L.

4. The long-term protective material for diversified grounding monitoring components of a power distribution system according to claim 3, characterized in that: The ultrasonic treatment time is 4-6h, and the power is 500-600W.

5. The long-term protective material for diversified grounding monitoring components of a power distribution system according to claim 4, characterized in that: The process parameters of the constant temperature heating reflux include: temperature 72-75° C., time 15-24 h.

Citation Information

Patent Citations

  • Anticorrosive coating with photocatalytic antibacterial effect as well as preparation method and application of anticorrosive coating

    CN115216201A

  • High-dispersity water-based carbon nanotube conductive slurry

    CN106046982A

  • Preparation of graphitic carbon nitride and application of the graphitic carbon nitride in water-based acrylic coating

    CN110606475A